PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP KINERJA KARYAWAN DENGAN INNOVATIVE BEHAVIOR SEBAGAI VARIABEL MEDIATOR di BPJS KETENAGAKERJAAN - Aries Zetni Hydayati (UNUSA Press, 2020)
The purpose of this study is to analyse the effect of transformational leadership on performance with innovative behaviour as a medium variable in achieving sustainable competitive advantages, the effect of transformational leadership on employees’ ability to innovate, the effect of employees’ innovation skills on their performance and the effect of transformational leadership on employees’ performance. The research approach uses quantitative technique. While data collection in this study is a survey method using Likert scale. The research data analysis will be using SEM analysis with SmartPLS version 3. The samples are 86 employees of membership section. Purposive sampling technique will be employed as samples fetching method. The results prove that there is a significant influence on transformational leadership style on employees’ performance with their innovation behaviour as an intermediate variable. Impact of transformational leadership style is found on employees’ innovation. There is an influence of employees’ innovation behaviour on their performance. Significant influence of transformational leadership style appears on employees’ performance